Characterization studies on Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes with new ligand`s derived from thiourea - Saad Dawood; Thana Yousif (College of Education for Pure Sciences, 2011)
Abstract complexes of the type [M(L1)Cl2] and [M(L2)Cl2] (M=Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II); L1=(2,11-dithioxo-1,3,10,12-tetra azacyclo octa deca-6,15-diene-4,9,13,18-tetraone), L2=(2,9-dithioxo-1,3,8,10-tetra aza cyclo tetra decane-4,7,11,14-tetraone) have been prepared and characterized by means of micro analysis (M) molar conductance measurements, magnetic susceptibility measurements, IR and electronic spectral. The prepared complexes may have an octahedral configuration.